Time-of-Flight and Structured Light Depth Cameras Technology and Applications - Zanuttigh, Pietro; Marin, Giulio; Dal Mutto, Carlo; Dominio, Fabio; Minto, Ludovico; Cortelazzo, Guido Maria; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides a comprehensive overview of the key technologies and applications related to new cameras that have brought 3D data acquisition to the mass market. It covers both the theoretical principles behind the acquisition devices and the practical implementation aspects of the computer vision algorithms needed for the various applications. Real data examples are used in order to show the performances of the various algorithms. The performance and limitations of the depth camera technology are explored, along with an extensive review of the most effective methods for addressing challenges in common applications. Applications covered in specific detail include scene segmentation, 3D scene reconstruction, human pose estimation and tracking and gesture recognition. This book offers students, practitioners and researchers the tools necessary to explore the potential uses of depth data in light of the expanding number of devices available for sale. It explores the impact of these devices on the rapidly growing field of depth-based computer vision.
Introduction -- Operating principles of structured light depth cameras -- Operating principles of Time-of-Flight depth cameras -- Calibration -- Data fusion from depth and standard cameras -- Scene segmentation assisted by data depth -- 3D scene reconstruction from depth camera data -- Human pose estimation and tracking -- Gesture recognition -- Conclusions.
Keywords: Computer science; Image processing; Pattern recognition; Computer Science; Image Processing and Computer Vision; Signal, Image and Speech Processing; Pattern Recognition; Electronic books